(18)F-FDG PET/CT in asymptomatic patients with COVID-19: the submerged iceberg surfaces - Colandrea, Marzia (Jpn J Radiol, 2020)
OBJECTIVE: The aim of this case series is to describe our experience in diagnosis and management of oncological asymptomatic patients with COVID-19 who underwent (18)F-FDG PET/CT. METHODS: From March 9 to March 31, 2020, we identified 5 patients who had PET/CT findings suspicious for COVID-19, but no symptom of infection. RESULTS: The first three patients were administered an SARS-CoV-2 test in a COVID-dedicated center, while the fourth and fifth were tested in our institution, in accordance with a new internal procedure. The SARS-CoV-2 test yielded positive results in all five patients. CONCLUSION: In this COVID-19 emergency, our task as radiologists and nuclear medicine physicians is to be able to identify imaging findings suggestive of the disease and to manage patients without overloading the hospital system.